A Comparative Study of Self-Regulation in Learning in Superior and Regular Classes in Thailand - Cahyani, Siti Nur; Rakhmawati, Dini; Lestari, Farika Wahyu (STAI Auliaurrasyidin Tembilahan, 2025)
Self-regulation in learning refers to an individual's ability to direct, monitor, and regulate their behavior, motivation, and emotions to achieve academic goals. However, not all students possess strong self-regulation skills in learning, as observed in superior classes. Students in regular classes tend to procrastinate more frequently, pay less attention to teachers, and struggle with learning. This study aims to investigate the differences in self-regulation in learning between students in regular and superior classes. The study employs a quantitative approach with a comparative design. The research participants comprise 68 sixth-grade students at Phatnawitya School, Thailand, with a sample of 45 students selected through cluster sampling. The research instrument consists of a self-regulation learning scale with 12 validated statements assessed using SPSS Statistics 26. This scale includes three aspects: metacognition, motivation, and behavior. Data analysis using an independent t-test revealed a significance value of 0.177 (p > 0.05), indicating no significant differences in self-regulation between students in superior and regular classes.